The Relationship between Maniac Types and Leisure Satisfaction among Participants in Marine Leisure Sports - Chun-Ho Yang, Myoung-Kyu Choi (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: This research was performed to examine the relationship between maniac types and leisure satisfaction, and, based on the findings review the results of participants in marine leisure sports.